Isolation, biochemical and molecular identification and investigation of probiotic potential of chicken intestine Bifidobacteria in rural areas of Ardabil province - Aalipanah, Sorour; Akhavan Sepahi, Abbas; Fazeli, Mohammadreza; Shariatmadari, Farid (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: More than a century after discovering probiotic strains, the food and dairy industries are increasingly looking to improve their products with these beneficial bacteria. This study aimed to analyze the potential characteristics of Iranian native probiotics and evaluate the safety of native probiotic Bifidobacterium isolated from the intestines of local chickens to discover the production potential of additives for food and dairy industries and feed. Materials and Methods: After sampling and preparing serial dilution, the samples were identified using biochemical tests. To confirm probiotics, growth ability was performed at different pHs, dilutions of bile salts and NaCl, isolated antimicrobial activity against common pathogens, and antibiotics susceptibility. Finally, the optimal strains were identified by molecular methods. Results: Four strains of the 15 gram-positive catalase-negative strains were biochemically similar to Bifidobacterium. Themes grew at PH 3-9 and different concentrations of bile salt and NaCl. These bacteria also had antimicrobial activity against common pathogens and were resistant to many antibiotics. Strains E1 and E4 had better probiotic properties. Finally, the molecular test showed that strains E1 and E4 were 100% similar to Bifidobacterium animalis and Bifidobacterium langum, respectively. Conclusions: The intestines of local chickens in Ardabil province contain probiotic bacteria such as Bifidobacterium animalis and Bifidobacterium langum. Therefore, these bacteria can be used in the food and dairy industries and improve livestock and poultry feed